2011
DOI: 10.1177/0309133311403538
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and processes of global shrub expansion

Abstract: Shrub expansion is a global phenomenon that is occurring on savannas, rangelands, and grasslands. In addition, this is an increasingly documented occurrence in the Arctic. Numerous recent studies have strived to pinpoint the drivers of this phenomenon, quantify the changes, and understand their implications for regional and global land use, disturbance regimes, and nutrient cycling. Inquiry into these topics has been facilitated by recent technological developments in satellite remote sensing, aerial photograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
136
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(153 citation statements)
references
References 162 publications
10
136
1
1
Order By: Relevance
“…This 'shrubification' is consistent with that previously reported in Alaska 5 and across the Arctic in general 6 . Such increases in shrub abundance might boost the productivity and CO 2 uptake of tundra ecosystems.…”
Section: Long-term Effects Of Permafrost Thawsupporting
confidence: 91%
“…This 'shrubification' is consistent with that previously reported in Alaska 5 and across the Arctic in general 6 . Such increases in shrub abundance might boost the productivity and CO 2 uptake of tundra ecosystems.…”
Section: Long-term Effects Of Permafrost Thawsupporting
confidence: 91%
“…Another possibility is shrub encroachment, a widespread phenomena in both temperature and moisture limited grasslands where native grasses are being progressively replaced by shrub vegetation (e.g., [78]). Shrub encroachment has been documented in many regions dominated by pasture ecosystems, including North America, Africa, Australia, and South America (see [79] for a review). Initial research indicated that shrub encroachment caused reduced productivity and an overall loss of ecosystem function [18,80].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of woody plants (encroachment or thickening) has been widely documented across many of the world's drylands (Ravi et al, 2009;Naito and Cairns, 2011). Encroachment has substantial effects on ecosystem properties and functions including soil hydrological properties and water balance (Nie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%